JANJI SUCI YANG TERKOYAK OLEH PIHAK KETIGA: PERLINDUNGAN KONSUMEN ATAS INTERVENSI POLIS ASURANSI KESEHATAN BERBASIS CO-PAYMENT OLEH OTORITAS JASA KEUANGAN (OJK) DITINJAU DARI TEORI KEPASTIAN HUKUM - Wijaya Nugroho, Robert; Elsina L, Rosalinda (Penerbit Lafadz Jaya, 2025)
This study examines the legal implications of the Financial Services Authority (OJK) Circular Letter No. 7 of 2025, which mandates a 10% Co-Payment system for all health insurance policyholders, including existing policies. Although the regulation aims to curb medical inflation and prevent moral hazard, it has sparked controversy for violating the principle of pacta sunt servanda—agreements must be kept—and for reducing consumer rights without consent. Using a normative legal approach, this research analyzes the legal standing of the circular within the framework of legal certainty and consumer protection theories. The findings indicate that Circular Letter 7/25 potentially exceeds its administrative authority, creates legal uncertainty, and contradicts the principles of consumer protection as stipulated in the Consumer Protection Law, the OJK Law, and the Insurance Law. The study emphasizes the need for a policy review to ensure a balance between the interests of the insurance industry and public welfare. It recommends that OJK coordinate with relevant ministries to address medical inflation through national healthcare cost regulation rather than by transferring additional financial burdens to policyholders.